2007
DOI: 10.1103/physreve.76.019901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Symmetry-based determination of space-time functions in nonequilibrium growth processes [Phys. Rev. E74, 061604 (2006)]

Abstract: The values of the nonuniversal constants 2 and D given in Table I of our paper are erroneous. Here we give the correct values of these quantities for the studied models ͑the Family model and the restricted Family model͒ in 1+1 and 2+1 dimensions ͓see Table I͔. Interestingly, the two models only differ through the value of the diffusion constant 2 . In Figs. 1-3 of our paper, we compared the numerically determined scaling function of the space-time correlation function with the exact solution Eq. ͑19͒ of the Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(96 citation statements)
references
References 0 publications
6
90
0
Order By: Relevance
“…In more general terms, it is known that the different symmetries of statistical mechanical models influence their scaling properties [42,43]. It would be interesting to understand in complete generality the interplay among the symmetries of a physical model in a static domain and the asymmetric presence of dilution when we let this domain grow in time.…”
Section: The Kardar-parisi-zhang Equationmentioning
confidence: 99%
“…In more general terms, it is known that the different symmetries of statistical mechanical models influence their scaling properties [42,43]. It would be interesting to understand in complete generality the interplay among the symmetries of a physical model in a static domain and the asymmetric presence of dilution when we let this domain grow in time.…”
Section: The Kardar-parisi-zhang Equationmentioning
confidence: 99%
“…The dynamics of non-interacting directed lines in the absence of disorder can be directly mapped to the one-dimensional Edwards-Wilkinson interface growth model (which is in turn equivalent to a free noisy diffusion equation). The two-time height-height autocorrelation function (5) in the correlated regime is found to be [42] C(t, s) = C 0 s 1/2 t s + 1…”
Section: Magnetic Field Quenches a Non-interacting Vortex Lines mentioning
confidence: 99%
“…In the free diffusive EdwardsWilkinson regime, the scaling exponent is b = 1/2 [32,42]. In our Langevin molecular dynamics study, we first analyze this case of free non-interacting vortex lines and start with the fixed magnetic field scenario to validate our numerical code.…”
Section: Magnetic Field Quenches a Non-interacting Vortex Lines mentioning
confidence: 99%
“…It has been noted in the past 14,35 that space-and timedependent quantities are often better suited than quantities that only depend on time if one aims at studying the scaling properties of an aging system. Taking into account what we learned from the autocorrelation, namely, that the correct growth law L͑t͒ has to be used and that the observed simple scaling behavior means that the exponent B = 0, we should have that the autocorrelation function C͑t , s , r͒ is only a function of L͑t͒ / L͑s͒ and r / L͑t͒ ͓or, alternatively, of L͑t͒ / L͑s͒ and r / L͑s͔͒,…”
Section: Space-time Correlation Functionmentioning
confidence: 99%
“…For systems undergoing phase ordering ͑as, for example, the perfect kinetic Ising model͒ it is usually found that b = 0, see Ref. 18 but some other classes of systems, for example, nonequilibrium growth systems, 35,36 are known to have b 0.…”
Section: Model and Measured Quantitiesmentioning
confidence: 99%